Аналіз та інтерпретація абсурдистського тексту (на матеріалі драматичної творчості К. І. Галчинського) - Моклиця, Андрій; Moklytsia, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядається цикл театральних мініатюр К. І. Галчинського «Зелена гуска» в аспекті поетики абсурдизму. Попри те, що твори автора можна визначити як абсурдні, або навіть абсурдистські, вони концептуально відрізняються від того, що ми називаємо театром абсурду. Основні аргументи на користь цієї тези - відсутність у К. Галчинського екзистенціалістського підґрунтя і домінантна роль комізму при побудові тексту. The article deals with the cycle of theatrical miniatures of famous Polish writer K.I. Galchinsky "Green Goose". Texts are analyzed in terms of the poetics of absurdism, and the key is the following thesis: Galchinsky's minidrama built on the principle of the absurd, but only superficially connected with theater of the absurd, because the lack of existentialist philosophical grounds. Moreover, the principle of the comic is to Galchinsky a major, while for the theater of the absurd is a secondary phenomenon. The dramatic works of the writer dominated by satirical intention. With the help of the absurd, the grotesque and humor Galchinsky completely destroys the key principles of the dramatic genre, and thus, tries to break the system of traditional values of the reader, to sow doubts about the authorities, to rethink the literary heritage of mankind.
Analysis and Interpretation of Absurdist Text (on the Material of the Dramatic Creativity К. I. Galchinsky)
Keywords: абсурд; абсурдистский стиль; absurd; absurdist style